Cryogenic design of FRIB cryomodule and distribution system and the present status. Issue 1 (March 2020) - Ganni, V; Knudsen, P; Casagrande, F; Jones, S
Abstract: The Michigan State University (MSU) Facility for Rare Isotope Beams (FRIB) accelerator utilizes six types of cryo-modules that are being installed in three Linac segments in the FRIB tunnel. The cryomodules contain both superconducting RF cavities and solenoid magnets with 2 K and 4.5 K refrigeration loads (respectively), magnet lead flow loads and 35-55 K shield loads and power coupler intercept loads. The first Linac segment (LS-1) with fifteen cryomodules was commissioned at 4.5 K and at 2 K. Commissioning experiences and some salient features of the cryogenic design of the cryomodules and the helium distribution systems will be discussed.